The Role of Teachers as Philosophers in Madrasah Education - Nasution, Abdul Fattah; Hasibuan, Rokiba; Yuslinda; Lubis, Leli Hasanah; Damanik, Sri Hayati (EDUTEC : Journal of Education And Technology, 2024)
This study analyzes the role of teachers as philosophers at MAS Babul Khairat, focusing on their teaching practices and the challenges they encounter. The findings indicate that teachers at this madrasah serve not only as academic instructors but also as moral and intellectual mentors, integrating Islamic values into their teaching. They employ various innovative methods, such as discussions, group projects, and problem-based learning approaches, to foster critical and reflective thinking among students. Additionally, teachers act as role models through their daily conduct, helping students to understand and apply ethical values in their lives. However, the study also identifies several challenges faced by these teachers, including limited resources, heavy workloads, insufficient professional development opportunities, and the pressure to meet high academic standards. These challenges underscore the need for increased support from both the school and the government, including restructuring teacher responsibilities, enhancing educational resources, and providing ongoing professional training. With appropriate support, teachers at MAS Babul Khairat can continue to develop effective and innovative teaching practices, further fulfilling their role as philosophers. This study highlights that with strong commitment and adequate support, teachers can cultivate a learning environment conducive to the intellectual, moral, and spiritual growth of students.